Novel Insights Into the Phylogeny and Biotechnological Potential of Weissella Species - Fanelli, Francesca; Montemurro, Marco; Chieffi, Daniele; Cho, Gyu-Sung; Franz, Charles M. A. P.; Dell'Aquila, Anna; Rizzello, Carlo Giuseppe; Fusco, Vincenzina (Frontiers in Microbiology, 2022)
In this study, the genomes of the Weissella (W.) beninensis, W. diestrammenae, W. fabalis, W. fabaria, W. ghanensis and W. uvarum type strains were sequenced and analysed. Moreover, the ability of these strains to metabolize 95 carbohydrates was investigated and the genetic determinants of such capability were searched within the sequenced genomes. 16S rRNA gene and genome based-phylogeny of all the Weissella species described to date allowed a re-assessment of the Weissella genus species groups. As a result, six distinct species groups within the genus, namely W. beninensis, W. kandleri, W. confusa, W. halotolerans, W. oryzae, and W. paramesenteroides species groups, could be described. Phenotypic analyses provided further knowledge about the ability of the W. beninensis, W. ghanensis, W. fabaria, W. fabalis, W. uvarum, and W. diestrammenae type strains to metabolize certain carbohydrates, and confirmed the interspecific diversity of the analyzed strains. Moreover, in many cases, the carbohydrate metabolism pathway and phylogenomic species group clustering overlapped. The novel insights provided in our study significantly improved the knowledge about the Weissella genus, and allowed us to identify features that define the role of the analysed type strains in fermentative processes and their biotechnological potential.